2014
DOI: 10.1177/1557988314555361
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Oncology Supports for Men

Abstract: Although men's cancer experiences have received limited attention within the field of psychosocial oncology, increasing attention is being devoted to the development and evaluation of men-centered programs. This scoping review describes this emergent body of literature, detailing the focus, participation, and impact of interventions designed to help men with cancer build illness-specific knowledge, adapt to illness, manage side effects, distress, and uncertainty, sustain relationships, and more. Striving to bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 132 publications
(278 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, although one third of the articles in this review did include male participants, there are still significant gaps in relation to studies encompassing masculinities. For example, previously identified aspects of male culture (e.g., men’s use of humor) did not surface in the results of the included studies (Wenger, Oliffe, & Bottorff, 2016). The characteristics of participants identified in this review is consistent with psychosocial interventions in rehabilitation and nursing literature (Dieperink, Wagner, Hansen, & Hansen, 2013; Oliffe, Ogrodniczuk, Bottorff, Hislop, & Halpin, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, although one third of the articles in this review did include male participants, there are still significant gaps in relation to studies encompassing masculinities. For example, previously identified aspects of male culture (e.g., men’s use of humor) did not surface in the results of the included studies (Wenger, Oliffe, & Bottorff, 2016). The characteristics of participants identified in this review is consistent with psychosocial interventions in rehabilitation and nursing literature (Dieperink, Wagner, Hansen, & Hansen, 2013; Oliffe, Ogrodniczuk, Bottorff, Hislop, & Halpin, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…There is a call for increased attention to the intersection of masculinity and cancer in psycho-oncology research with more emphasis on how the societal expectations of being a man intersects with experiences of cancer support (Wenger et al, 2014). The studies reported here address this intersection by examining the relationship of social constraints and restrictive emotionality with psychological distress in both young and older men with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging and inclusive styles of professional facilitation are recognized as important therapeutic factors in stimulating group interaction, cohesion, and belonging. [36] Although supportive/expressive goals framed the content of discussions, the (equally appreciated) ‘no agenda’ style of facilitation supported men to feel empowered over the process of shared narratives. This is consistent with the literature suggesting that SEGT, as a semistructured intervention, is designed to allow group members to steer the focus of the group discussions because they have the first‐hand experience with their own challenges.…”
Section: Discussionmentioning
confidence: 99%